DO DIFFERENT DISCUSSION ACTIVITIES IN DEVELOPING SCIENTIFIC ARGUMENTATION AFFECT STUDENTS’ MOTIVATION IN CHEMISTRY? - Sri Rahayu; Klaudia E.N Bambut; Fauziatul Fajaroh (LPMPP Universitas Negeri Yogyakarta, 2020)
Argumentation has an influence on students’ cognitive skills as well as learning motivation through the increase in confidence, science, and social activities. Argumentation skills can be trained through different patterns of discussion — cooperative and collaborative. This study aimed to reveal the learning motivation of students who enacted their argumentation skills using Argument-Driven Inquiry (ADI) with cooperative and collaborative discussions. The research design was a case study that engaged 95 Grade 11 students who were learning the chemical equilibrium topic. The research instrument employed was the ARCS motivation questionnaire that consisted of four aspects, namely attention, confidence, relevance, and satisfaction. The quantitative data were collected from the ARCS questionnaire and the qualitative data were collected from classroom observation, interview, and students’ discussion process. The data were analyzed using designed criteria and percentages, and were described qualitatively. The study found that students who learn chemistry through cooperative-ADI gain a high average motivation. For each aspect of motivation, the majority of students in the cooperative-ADI discussion show a higher level of motivation compared to students’ level in the collaborative-ADI discussion. The study has implications on how to design a discussion group in terms of motivation.